Pre-heating Temperature Effect on Electrochromic Properties of TiO2 Thin Films - Eldjilali, Cheikh Zakaria; Chan, Kah-Yoong; Tan, Ming-Yue; Abdelhamed, Abdelrahman Hamed Ebrahem; Thien, Gregory Soon How; Low, Pei-Ling; Sin, Yew-Keong; Lee, Chu-Liang; Pang, Wai-Leong (International Journal of Integrated Engineering, 2024)
Smart windows represent a promising technology that enables the selective transmission of light and heat, and electrochromism technology is gaining interest in smart window applications. Electrochromic (EC) smart windows are the preferred choice for outdoor applications due to their ability to withstand high temperatures. Particularly, Tungsten Trioxide (WO3) is commonly used as an electrochromic layer in EC devices. Although Titanium Dioxide (TiO2) is a less expensive EC material compatible with optoelectronics applications (including solar cells), it has received little research attention. In the course of this study, the sol-gel spin coating method was utilised to deposit a thin film of TiO2 onto Indium Tin Oxide (ITO). This technique was chosen for its simplicity, affordability, and ease of coating thin films. The pre-heating temperature demonstrated a critical role in sol-gel fabrication, particularly in electrochromic applications. As the impact of the pre-heating temperature remains poorly understood, this study effectively investigated the effect of various pre-heating temperatures on the performance of TiO2-based electrochromic thin films. Moreover, this study effectively analysed the structural, optical, and EC properties of the TiO2 thin films pre-heated at different temperatures.